Wealth inequality in Latin America - Rafael Carranza; Mauricio de Rosa; Ignacio Flores (Inter-American Development Bank (IDB), 2023)
How much wealth has accumulated in the region and how is it distributed across households? Despite being widely recognized for its extreme income inequality, reliable data on wealth is scarce, partial and oftentimes contradictory, making it difficult to an swer these ba sic qu estions. In this study, we es timate ag gregates based on macroeconomic data, and inequality based on recently available surveys. We contrast our results with the literature, with a handful of state-of-the-art estimates from administrative sources, and with more available but extrapolated estimates from Credit Suisse and wid.world. Considering all the evidence, we distinguish reliable facts from what can only be conjectured or speculated. We find that aggregate wealth increased over two decades in four countries, now ranging close to 3.5 the national income for market value estimates and 5-6 times at book values. We also find that wealth inequality is amongst the highest in the world were it can be measured. Given data limitations, one can only speculate about aggregates in opaque countries and about inequality trends in any country in the region. Although recent research in the developed world has focused in combining data sources to better understand wealth, the region lags behind and urgently requires more and better public information.
Keywords: D31; E01; E22; 330; wealth distribution; wealth-to-income ratios; household surveys; national accounts; Latin America